Aging, Cellular Senescence, and Progressive Multiple Sclerosis - Papadopoulos, Dimitrios; Magliozzi, Roberta; Mitsikostas, Dimos D.; Gorgoulis, Vassilis G.; Nicholas, Richard S. (Frontiers in Cellular Neuroscience, 2020)
Ageing is one of the most important risk factors for the development of several neurodegenerative diseases including progressive multiple sclerosis (MS). Cellular senescence (CS) is a key biological process underlying ageing. Several stressors associated with ageing and MS pathology such as oxidative stress, mitochondrial dysfunction, cytokines and replicative exhaustion are known triggers of CS. Senescent cells exhibit stereotypical metabolic and functional changes, which include cell-cycle arrest and acquiring a pro-inflammatory phenotype secreting cytokines, growth factors, metalloproteinases and reactive oxygen species. They accumulate with ageing and can convert neighboring cells to senescence in a paracrine manner. In MS, accelerated cellular senescence may drive disease progression by promoting chronic non-remitting inflammation, loss or altered immune, glial and neuronal function, failure of remyelination, impaired blood-brain barrier integrity and ultimately neurodegeneration. Here we discuss the evidence linking cellular senescence to the pathogenesis of MS and the putative role of senolytic and senomorphic agents as neuroprotective therapies in tackling disease progression.